Conductive composition
By using a conductive composition containing silicone auxiliary agent in the conductive coating film, the high current density and stability of the conductive coating film in the prior art is solved, and efficient electrochemical performance and physical stability are achieved.
Patent Information
- Application Number
- JP2023150000
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-28
AI Technical Summary
It is difficult to form a conductive coating film with high current density and excellent physical and electrochemical stability in the prior art.
A conductive composition comprising a silicone adjuvant is used, which consists of conductive diamond particles, non-particle type conductive adjuvant and binder.
High current density and excellent physical and electrochemical stability are achieved to ensure the stability and durability of coated films at high voltages.
Smart Images

Figure 2025042837000001 
Figure 2025042837000002 
Figure 2025042837000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrically conductive composition, and more particularly to an electrically conductive composition capable of forming an electrically conductive coating film having high current density and excellent physical and electrochemical stability. [Background technology]
[0002] Conductive diamond particles are physically and chemically stable, and therefore are expected to be an electrode material capable of suppressing background current. A representative conductive diamond particle is boron-doped diamond, which is diamond doped with boron. As a method for manufacturing an electrode containing boron-doped diamond, a method for forming a thin film of boron-doped diamond on a metal substrate by chemical vapor deposition (CVD) is exemplified (Patent Document 1). However, in the chemical vapor deposition method, it is difficult to form a pattern using boron-doped diamond, and since the reaction must be carried out in a vacuum state, it is difficult to form a large electrode. There is also a problem that the film formed by the chemical vapor deposition method is a thin film and therefore easily peels off.
[0003] Other than the chemical vapor deposition method, a method is known in which a composition containing boron-doped diamond and a binder is applied onto a substrate to form a conductive coating containing boron-doped diamond (Patent Documents 2 to 4). Although these methods can solve the problems associated with the chemical vapor deposition method, the current density and physical and electrochemical stability of the resulting electrodes are insufficient. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2007-238989 A [Patent Document 2] Patent Publication No. 2022-089096 [Patent Document 3] JP 2018-076216 A [Patent Document 4] JP 2020-199478 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a conductive composition capable of forming a conductive coating film having high current density and excellent physical and electrochemical stability. [Means for solving the problem]
[0006] The inventors have discovered that a conductive composition containing boron-doped diamond, a binder, and a conductive material of a specific shape can form a conductive coating film with high current density and excellent physical and electrochemical stability, and have completed the present invention.
[0007] That is, the present invention includes the following aspects. <1> A conductive composition comprising conductive diamond particles, a conductive assistant comprising a non-particulate conductive component, and a binder.
[0008] <2> When a 3.3 μm-thick conductive coating film made of the conductive composition formed on a substrate was used as a test electrode and a constant current electrolysis test was carried out for 90 minutes in a 0.1 M sodium sulfate aqueous solution, a constant current of 11 mA / cm was obtained. 2 Item 2. The conductive composition according to item 1, wherein the potential is 5 V vs. Ag / AgCl or less even at a constant current of 10 V or less.
[0009] <3> Item 3. The conductive composition according to item 1 or 2, wherein the conductive diamond particles are boron-doped diamond.
[0010] <4> 3. The conductive composition according to item 1 or 2, comprising 0.01 to 800 parts by weight of a conductive assistant relative to 100 parts by weight of conductive diamond particles.
[0011] <5> Item 3. The conductive composition according to item 1 or 2, wherein the conductive assistant comprises at least one selected from the group consisting of a conductive polymer, a carbon material, and a metal material.
[0012] <6> Item 6. The conductive composition according to item 5, wherein the conductive polymer is one or more selected from the group consisting of polythiophene, polypyrrole, and polyaniline.
[0013] <7> Item 6. The conductive composition according to item 5, wherein the carbon material is one or more selected from the group consisting of carbon nanotubes, graphene, and graphite.
[0014] <8> Item 6. The conductive composition according to item 5, wherein the metal material is one or more selected from the group consisting of silver nanowires, copper nanowires, and gold nanowires.
[0015] <9> Item 3. A conductive coating film comprising the conductive composition according to item 1 or 2. Effect of the Invention
[0016] The conductive composition of the present invention can form a conductive coating film that has a high current density and is excellent in physical and electrochemical stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] <<Conductive composition>> The conductive composition of the present invention is characterized by containing conductive diamond particles, a conductive assistant consisting of a non-particulate conductive component, and a binder.
[0018] <Conductive diamond particles> Conductive diamond particles have both the physical and chemical stability derived from diamond and electrical conductivity. Since diamond itself is a non-conductive material, electrical conductivity is achieved by forming a complex between diamond and a doping element. Examples of such conductive diamond particles include boron-doped diamond particles (BDDP), nitrogen-doped diamond particles, and phosphorus-doped diamond particles. Among these, boron-doped diamond particles (BDDP) are preferred because of their high electrical conductivity.
[0019] The conductive diamond particles preferably comprise a particulate substrate containing diamond and a layer containing a doping element consisting of boron, nitrogen, or phosphorus present on at least a part of the surface of the particulate substrate. The particulate substrate may have a film made of diamond present on at least a part of its surface, and it is preferable that the entire surface is covered with a film made of diamond. A part of the surface of the particulate substrate may be covered with a diamond film, or the entire surface of the particulate substrate may be covered with a diamond film. Materials used for the particulate substrate include natural or synthetic diamond particles, metal fine particles such as silicon or molybdenum, metal alloy fine particles such as boron nitride, metal oxide fine particles such as quartz or alumina, etc., but natural or synthetic diamond particles are preferred. Synthetic diamond particles can be produced by CVD methods such as thermal CVD, RF plasma CVD, and hot filament CVD, PVD methods such as ion beam method and ionized deposition method, high temperature and high pressure method, etc.
[0020] The particle diameter (D50, median diameter) of the particulate base material is not particularly limited, but is preferably from 1 nm to 50 μm, more preferably from 1 nm to 5 μm, and even more preferably from 1 nm to 500 nm.
[0021] The layer containing the doping element can be formed on the surface of the particulate substrate by a CVD method such as plasma CVD, thermal CVD, photo CVD, or laser CVD. The layer containing the doping element preferably contains carbon in addition to the doping element. In the layer containing the doping element, the ratio of the number of atoms of the doping element to the number of atoms of carbon (doping element / carbon) is preferably 10 to 100,000 ppm, more preferably 100 to 50,000 ppm. Within this range, conductive diamond particles with excellent crystallinity and conductivity can be obtained.
[0022] Examples of carbon sources that can be used when forming a layer containing a doping element by a CVD method include aliphatic hydrocarbons such as methane, ethane, propane, butane, pentane, hexane, heptane, and octane; alicyclic hydrocarbons such as cyclohexane; aromatic hydrocarbons such as benzene, toluene, xylene, and ethylbenzene; alcohols such as methanol, ethanol, isopropyl alcohol, and butanol; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; ethers such as diethyl ether, dimethoxyethane, tetrahydrofuran, and dioxane; and esters such as methyl acetate, ethyl acetate, isopropyl acetate, and butyl acetate.
[0023] Examples of materials containing a doping element used when forming a layer containing a doping element by a CVD method, when the doping element is boron, include boron oxide, boron carbide, boron nitride, boric acid, diborane, triethylborane, trimethoxyborane, triethoxyborane, tripropoxyborane, and tri(1,1-dimethylethoxy)borane.
[0024] The average particle size of the conductive diamond particles is preferably 5 nm to 10 μm, and more preferably 50 nm to 1 μm. When the average particle size is 5 nm or more, the crystallinity tends to be good. When the average particle size is 10 μm or less, the dispersibility of the conductive diamond particles in the conductive composition tends to be good. The average particle size of the conductive diamond particles is the volume average particle size measured by dynamic light scattering (DLS).
[0025] The content of the doping element in the conductive diamond particles is preferably 0.01 to 10% by weight, more preferably 0.02 to 7% by weight, and even more preferably 0.03 to 5% by weight. Within these ranges, the conductivity tends to be excellent.
[0026] The shape of the conductive diamond particles is not particularly limited, and examples thereof include spherical, polyhedral, needle, spindle, etc. The conductive diamond particles preferably have a conductivity of 0.01 S / cm or more in powder form.
[0027] In the total solid content of the conductive composition, the solid content of the conductive diamond particles is preferably 0.01 to 90% by weight, more preferably 0.05 to 80% by weight, and even more preferably 0.2 to 75% by weight. When the solid content of the conductive diamond particles is within the above range, it tends to be electrochemically stable.
[0028] <Conductive assistant> The conductive assistant contributes to form a conductive coating film with excellent conductivity. The mechanism of improving conductivity includes that the conductive assistant interacts with conductive diamond particles to form a conductive path, and that the conductive assistant improves the conductivity at the interface between conductive diamond particles and binder, but the present invention is not limited to these mechanisms.
[0029] The conductive assistant is non-particulate in order to improve the conductivity of the conductive coating film. Specific shapes include fiber, plate, plate, and scale. The aspect ratio of the conductive assistant is preferably 10 or more, more preferably 100 or more, and even more preferably 1000 or more. The upper limit of the aspect ratio is not particularly limited, but can be 500000. The aspect ratio of the conductive assistant can be calculated by calculating the major axis / minor axis from the major axis and minor axis of the conductive assistant.
[0030] The material constituting the conductive assistant is not particularly limited as long as it has conductivity, and examples of the material include conductive polymers, carbon materials, and metal materials.
[0031] In the conductive composition, the amount of the conductive assistant is preferably 0.01 to 800 parts by weight, more preferably 0.1 to 800 parts by weight, and even more preferably 0.3 to 700 parts by weight, per 100 parts by weight of the conductive diamond particles. Within these ranges, the resulting conductive coating film tends to be physically and electrochemically stable.
[0032] <Conductive polymer> As the conductive polymer, a conventionally known conductive polymer can be used, for example, polythiophene, polypyrrole, polyaniline, polyacetylene, polyphenylenevinylene, polynaphthalene, derivatives thereof, and complexes of these with dopants. These conductive polymers may be used alone or in combination of two or more. Among these, conductive polymers having polythiophene in the molecule are preferred because of their excellent conductivity.
[0033] As the conductive polymer having polythiophene in the molecule, poly(3,4-disubstituted thiophene) or a complex of poly(3,4-disubstituted thiophene) and a polyanion is more preferable because it has excellent conductivity and chemical stability, and can form a conductive coating film at low temperature in a short time, resulting in excellent productivity.
[0034] As the poly(3,4-disubstituted thiophene), poly(3,4-dialkoxythiophene) or poly(3,4-alkylenedioxythiophene) is particularly preferred. As the poly(3,4-dialkoxythiophene) or poly(3,4-alkylenedioxythiophene), the following formula (I):
[0035] [ka]
[0036] Preferred is a cationic form of polythiophene consisting of repeating structural units of the formula: 1 and R 2 are each independently a hydrogen atom or C 1-4 or R 1 and R 2 When C is bonded 1-4 C represents an alkylene group. 1-4 The alkyl group of R is not particularly limited, but examples thereof include a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, and a t-butyl group. 1 and R 2 If C is bonded 1-4The alkylene group in is not particularly limited, but examples thereof include a methylene group, a 1,2-ethylene group, a 1,3-propylene group, a 1,4-butylene group, a 1-methyl-1,2-ethylene group, a 1-ethyl-1,2-ethylene group, a 1-methyl-1,3-propylene group, and a 2-methyl-1,3-propylene group. Among these, a methylene group, a 1,2-ethylene group, and a 1,3-propylene group are preferred, and a 1,2-ethylene group is more preferred. 1-4 and C 1-4 The alkylene group may have some of its hydrogen atoms substituted. 1-4 As the polythiophene having an alkylene group, poly(3,4-ethylenedioxythiophene) is particularly preferred.
[0037] The polyanion forms a complex with the polythiophene by forming an ion pair, and the polythiophene can be stably dispersed in water. The polyanion is not particularly limited, but examples thereof include carboxylic acid polymers such as polyacrylic acid, polymaleic acid, and polymethacrylic acid, and sulfonic acid polymers such as polystyrene sulfonic acid, polyvinyl sulfonic acid, and polyisoprene sulfonic acid. These carboxylic acid polymers and sulfonic acid polymers may also be copolymers of vinyl carboxylic acids and vinyl sulfonic acids with other polymerizable monomers, such as acrylates, styrene, and aromatic vinyl compounds such as vinyl naphthalene. Among these, polystyrene sulfonic acid is particularly preferred.
[0038] The weight-average molecular weight of the polystyrene sulfonic acid is preferably 20,000 to 500,000, and more preferably 40,000 to 200,000. If polystyrene sulfonic acid with a molecular weight outside this range is used, the dispersion stability of the polythiophene-based conductive polymer in water may decrease. The weight-average molecular weight is a value measured by gel permeation chromatography (GPC).
[0039] The conductive polymer is particularly preferably a complex of poly(3,4-ethylenedioxythiophene) and polystyrenesulfonic acid having a conductivity of 0.01 S / cm or more, because a conductive coating film formed from a conductive composition containing such conductive particles has particularly excellent transparency and conductivity.
[0040] The average particle size of the conductive polymer is preferably 5 to 1000 nm, more preferably 10 to 800 nm, and even more preferably 20 to 600 nm. Within the above range, the conductive polymer tends to have excellent conductivity, dispersion stability, and transparency. The average particle size is the particle size at 50% cumulative volume (D50) measured by dynamic light scattering.
[0041] <Carbon materials> Examples of the carbon material include carbon nanotubes, graphene, and graphite.
[0042] The carbon nanotubes are not particularly limited, and carbon nanotubes manufactured by arc discharge, laser evaporation, chemical vapor deposition (CVD), etc. can be used. Single-walled carbon nanotubes, double-walled carbon nanotubes, multi-walled carbon nanotubes, and mixtures thereof can all be used. In terms of excellent electrical conductivity, it is preferable to include single-walled carbon nanotubes.
[0043] The length of the carbon nanotubes is preferably 1 to 2000 μm, more preferably 5 to 1000 μm, and even more preferably 5 to 500 μm. Within the above range, there is a tendency for excellent conductivity and transparency to be achieved in the conductive coating film.
[0044] The diameter of the carbon nanotube is preferably 0.5 to 20 nm, and more preferably 1 to 10 nm, in the case of a single-walled carbon nanotube. Within the above range, there is a tendency that excellent conductivity and transparency can be achieved in the conductive coating film.
[0045] Graphene is a single-layer substance in which carbon atoms bonded by sp2 bonds are arranged two-dimensionally. Graphite is a substance in which many graphenes are laminated. The average particle size of graphene or graphite is preferably 0.3 to 500 μm, more preferably 0.5 to 100 μm. The average particle size can be measured by a particle size distribution measuring device.
[0046] <Metal materials> Examples of the metal material include metal nanowires and scale-like metal flakes. Examples of the metal nanowires include those made of a metal element or a metal-containing compound having electrical conductivity. Examples of the metal element include silver, copper, silver, iron, cobalt, nickel, zinc, ruthenium, rhodium, palladium, cadmium, osmium, iridium, platinum, etc., and silver, copper, and gold are preferred. Examples of the metal-containing compound include those containing the above-mentioned metals.
[0047] The length of the metal nanowires is preferably 1 to 2000 μm, more preferably 5 to 1000 μm, and even more preferably 5 to 500 μm. Within the above range, there is a tendency that excellent conductivity can be achieved in the conductive coating film.
[0048] The metals mentioned for the metal nanowires can be used as the constituent material for the scaly metal flakes. The diameter of the scaly metal flakes is preferably 1 to 2000 μm, and more preferably 5 to 1000 μm.
[0049] <Binder> The material constituting the binder is not particularly limited, but resin is preferable. Thermoplastic resins and thermosetting resins can be used as the resin. Examples of thermoplastic resins include acrylic resins, polyurethane resins, polyester resins, polyolefin resins, styrene resins, vinyl acetate resins, vinyl chloride resins, and fluorine resins. Examples of thermosetting resins include silicone resins, epoxy resins, phenol resins, amino resins, and polyimide resins, as well as thermoplastic resins having reactive functional groups. These binders have high compatibility with polythiophene conductive polymers, and conductive coating films made of conductive compositions containing these binders have good affinity for substrates. Furthermore, the binder contained in the conductive composition may be a water-dispersible resin or a curable resin that hardens after being applied to a substrate. When the binder is a water-dispersible resin, the water-dispersible resin may be one that is dispersed as a result of the addition of a hydrophilic functional group to the resin, or one that is forcibly dispersed by an emulsifier. These binders may be used alone, or two or more types may be used in combination.
[0050] Examples of acrylic resins include (meth)acrylic resins, vinyl ester resins, etc. These acrylic resins may be polymers containing, as constituent monomers, polymerizable monomers having an acid group such as a carboxyl group, an acid anhydride group, a sulfonic acid group, or a phosphoric acid group, and examples of such polymerizable resins include homopolymers or copolymers of polymerizable monomers having an acid group, and copolymers of polymerizable monomers having an acid group and copolymerizable monomers.
[0051] The (meth)acrylic resin may be polymerized with a copolymerizable monomer so long as it contains a (meth)acrylic monomer as a main constituent monomer (e.g., 50 mol % or more). In this case, at least one of the (meth)acrylic monomer and the copolymerizable monomer may have an acid group. Examples of the (meth)acrylic resin include (meth)acrylic monomers having an acid group [(meth)acrylic acid, sulfoalkyl (meth)acrylate, sulfonic acid group-containing (meth)acrylamide, etc.] or copolymers thereof, copolymers of (meth)acrylic monomers which may have an acid group and other polymerizable monomers having an acid group [other polymerizable carboxylic acids, polymerizable polycarboxylic acids or anhydrides, vinyl aromatic sulfonic acids, etc.] and / or copolymerizable monomers [e.g., (meth)acrylic acid alkyl esters, glycidyl (meth)acrylate, (meth)acrylonitrile, aromatic vinyl monomers, etc.], copolymers of other polymer monomers having an acid group and (meth)acrylic copolymerizable monomers [e.g., (meth)acrylic acid alkyl esters, hydroxyalkyl (meth)acrylates, glycidyl (meth)acrylate, (meth)acrylonitrile, etc.], rosin-modified urethane acrylates, specially modified acrylic resins, urethane acrylates, epoxy acrylates, urethane acrylate emulsions, and the like.
[0052] Among these (meth)acrylic resins, (meth)acrylic acid-(meth)acrylic acid ester polymers (acrylic acid-methyl methacrylate copolymers, etc.), (meth)acrylic acid-(meth)acrylic acid ester-styrene copolymers (acrylic acid-methyl methacrylate-styrene copolymers, etc.), and the like are preferred.
[0053] The polyurethane resin is not particularly limited as long as it is a polymer compound obtained by copolymerizing a compound having an isocyanate group and a compound having a hydroxyl group, and examples thereof include ester-ether polyurethane, ether polyurethane, polyester polyurethane, carbonate polyurethane, and acrylic polyurethane.
[0054] The polyester resin is not particularly limited as long as it is a polymer compound obtained by polycondensation of a compound having two or more carboxyl groups in the molecule and a compound having two or more hydroxyl groups, and examples thereof include polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and polybutylene naphthalate.
[0055] The polyolefin resin is not particularly limited, but examples thereof include polyethylene, polypropylene, chlorinated polypropylene, maleic anhydride-modified polypropylene, maleic anhydride-modified chlorinated polypropylene, ethylene-vinyl acetate copolymer, and the like.
[0056] The styrene-based resin is not particularly limited as long as it is a resin whose main component is styrene, and examples thereof include polystyrene, acrylonitrile-styrene copolymer (AS), and acrylonitrile-butadiene-styrene copolymer (ABS).
[0057] The vinyl acetate resin is not particularly limited as long as it is a resin obtained by polymerization of vinyl acetate, and examples thereof include polyvinyl acetate, ethylene-vinyl acetate copolymer, and the like.
[0058] The vinyl chloride resin is not particularly limited as long as it is a resin obtained by polymerization of vinyl chloride, and examples thereof include polyvinyl chloride, ethylene-vinyl chloride copolymer, vinyl chloride-vinyl acetate copolymer, and the like.
[0059] Examples of the fluorine-based resin include polytetrafluoroethylene, polyvinylidene fluoride, Teflon (registered trademark), and polyvinyl fluoride.
[0060] Examples of silicone-based resins include oligomers of alkoxysilanes formed by condensation of alkoxysilane monomers represented by the following formula (I) and having one or more siloxane bonds (Si—O—Si) in one molecule. SiR 1 4(I) (In the formula, R1 is hydrogen, a hydroxyl group, an alkoxy group having 1 to 4 carbon atoms, an alkyl group having 1 to 12 carbon atoms which may have a substituent, or an aryl group having 6 to 20 carbon atoms which may have a substituent. 1 At least one of these is an alkoxy group having 1 to 4 carbon atoms or a hydroxyl group.)
[0061] In formula (I), R 1 Examples of the alkoxy group include a methoxy group, an ethoxy group, a propoxy group, and a butoxy group. 1 Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, a normal butyl group, a tertiary butyl group, a pentyl group, and a hexyl group. 1 The aryl group includes a phenyl group, a tolyl group, and a benzyl group.
[0062] Specific examples of the monomer represented by formula (I) include 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, Examples of the isocyanate include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, methyltrimethoxysilane, phenyltrimethoxysilane, dimethyldimethoxysilane, methyltriethoxysilane, n-propyltrimethoxysilane, diisopropyldimethoxysilane, isobutyltrimethoxysilane, diisobutyldimethoxysilane, isobutyltriethoxysilane, n-hexyltrimethoxysilane, n-hexyltriethoxysilane, cyclohexylmethyldimethoxysilane, n-octyltriethoxysilane, n-decyltrimethoxysilane, tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane. Among these, tetramethoxysilane and tetraethoxysilane are preferred.
[0063] The structure of the silicone resin is not particularly limited, and may be linear or branched. The silicone resin may be a condensation product of one type of monomer represented by formula (I) or two or more types of monomers.
[0064] Specific examples of silicone resins include methyl silicate oligomer and ethyl silicate oligomer.
[0065] The weight average molecular weight of the silicone resin is not particularly limited, but is preferably 200 to 10,000, and more preferably 400 to 5,000.
[0066] Examples of epoxy resins include bisphenol A type, bisphenol F type, phenol novolac type, tetrakis(hydroxyphenyl)ethane type or tris(hydroxyphenyl)methane type which are multifunctional types having a large number of benzene rings, biphenyl type, triphenolmethane type, naphthalene type, ortho-novolac type, dicyclopentadiene type, aminophenol type, alicyclic epoxy resins, silicone epoxy resins, and the like.
[0067] Examples of the reactive functional group of the thermoplastic resin having a reactive functional group include a hydroxyl group, a carboxyl group, an acid anhydride group, a sulfonic acid group, a phosphoric acid group, and a glycidyl group.
[0068] The ratio of the solid content of the binder to the total solid content of the conductive composition is preferably 10 to 99% by weight, more preferably 15 to 95% by weight, and even more preferably 20 to 93% by weight. The content of the solid content of the binder is preferably 10 to 3000 parts by weight, more preferably 20 to 2500 parts by weight, per 100 parts by weight of the solid content of the conductive diamond particles. Within this range, the conductive coating film can have sufficient strength and conductivity.
[0069] <Method of manufacturing conductive composition> The conductive composition can be obtained by mixing conductive diamond particles, a conductive assistant consisting of a non-particulate conductive component, a binder, and, if necessary, any optional components described below in any order. The pH of the conductive composition can be adjusted by adding an inorganic acid such as sulfuric acid, hydrochloric acid, nitric acid, or phosphoric acid, an organic acid such as acetic acid, formic acid, or benzoic acid, or an alkaline agent such as NaOH or KOH.
[0070] In order to improve the dispersibility of conductive diamond particles, conductive assistants, etc., conductive diamond particles, conductive assistants, etc. may be dispersed in water or organic solvent in the presence of a dispersant described later. Dispersion can be performed using, for example, a vibration mill, a planetary mill, a ball mill, a bead mill, a sand mill, a jet mill, a roll mill, a homogenizer, an ultrasonic homogenizer, a high-pressure homogenizer, an ultrasonic device, etc. In order to obtain a conductive composition that can realize high conductivity and transparency, it is preferable to perform dispersion using an ultrasonic homogenizer or a high-pressure homogenizer.
[0071] In addition, before the dispersion treatment, the conductive diamond particles, conductive assistant, etc. may be subjected to a high-speed stirring treatment as a pretreatment. The high-speed stirring treatment is a dispersion treatment under relatively lower intensity conditions than the dispersion treatment using an ultrasonic homogenizer, etc., and has the effect of loosening the aggregation of the conductive diamond particles, conductive assistant, etc. by the high-speed rotation of the stirring body.
[0072] Furthermore, if necessary, agglomerates of the conductive diamond particles, conductive assistant, etc., and impurities may be removed by centrifugal separation or filtering.
[0073] <Optional ingredients> The conductive composition may contain, in addition to the conductive diamond particles, the conductive assistant consisting of a non-particulate conductive component, and the binder, a solvent, an antioxidant, a leveling agent, a dispersant, a crosslinking agent, a catalyst, etc.
[0074] <Solvent> Examples of the solvent include water; alcohols such as methanol, ethanol, 2-propanol, and 1-propanol; ethylene glycols such as ethylene glycol, diethylene glycol, trimethylene glycol, triethylene glycol, and tetraethylene glycol; glycol ethers such as ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, ethylene glycol diethyl ether, and diethylene glycol dimethyl ether; glycol ether acetates such as ethylene glycol monoethyl ether acetate, diethylene glycol monoethyl ether acetate, and diethylene glycol monobutyl ether acetate; propylene glycols such as propylene glycol, dipropylene glycol, and tripropylene glycol; propylene glycol ethers such as propylene glycol monoethyl ether, dipropylene glycol monomethyl ether, propylene glycol dimethyl ether, and propylene glycol diethyl ether; propylene glycol ethers such as propylene glycol monomethyl ether acetate, and propylene glycol monomethyl ether acetate. ether acetates; ethers such as diethyl ether, diisopropyl ether, methyl t-butyl ether, and tetrahydrofuran; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; hydrocarbons such as toluene, xylene (o-, m-, or p-xylene), hexane, and heptane; esters such as butyl acetate; halogens, acetonitrile, N-methylformamide, N,N-dimethylformamide, γ-butyrolactone, and N-methylpyrrolidone; amides such as 1,4-butanediol, 1,5- Examples of the compound include hydroxyl group-containing compounds such as pentanediol, 1,6-hexanediol, neopentyl glycol, catechol, cyclohexanediol, cyclohexanedimethanol, glycerin, diethylene glycol monoethyl ether, and propylene glycol monomethyl ether; carbonyl group-containing compounds such as isophorone, propylene carbonate, cyclohexanone, acetylacetone, ethyl acetate, ethyl acetoacetate, methyl orthoacetate, and ethyl orthoformate; and compounds having a sulfo group such as dimethyl sulfoxide.
[0075] Among these, water, alcohols, ethylene glycols, and compounds having a sulfo group are preferred, water, ethanol, ethylene glycol, and dimethyl sulfoxide are more preferred, and a mixed solvent of water and ethanol, ethylene glycol, or dimethyl sulfoxide is even more preferred. In the mixed solvent, the amount of water is preferably 20% by weight or more, more preferably 50% by weight or more, even more preferably 75% by weight or more, and particularly preferably 95% by weight or more and less than 100%. It is preferable that the solvent does not remain in the conductive coating film formed using the conductive composition.
[0076] The solid content of the conductive composition can be adjusted by the blending amount of the solvent. The solid content of the conductive composition is not particularly limited, but is preferably 0.1 to 50% by weight, more preferably 0.5 to 30% by weight, and even more preferably 1 to 20% by weight. When the solid content is within the above range, sufficient conductivity can be exhibited, and the coating property during the production of the conductive coating film and the storage stability of the conductive composition tend to be good. In this specification, there is no particular distinction between a substance that completely dissolves all the components of the conductive composition (i.e., a "solvent") and a substance that disperses the insoluble components (i.e., a "dispersion medium"), and both are described as "solvent".
[0077] <Antioxidants> By blending an antioxidant in the conductive composition, the heat resistance, moist heat resistance, and ultraviolet resistance of the conductive coating film can be improved. The antioxidant may be either a water-soluble antioxidant or an oil-soluble antioxidant.
[0078] The content of the antioxidant in the conductive composition is preferably 0.5 to 25% by weight, more preferably 1 to 20% by weight, based on the total solid content. Within these ranges, the conductive coating film can be provided with excellent durability, conductivity, and optical properties. In addition, the stickiness of the conductive coating film can be suppressed.
[0079] <Dispersant> A dispersant may be added to improve the dispersibility of the conductive diamond particles and the conductive assistant. Examples of the dispersant include cationic dispersants, anionic dispersants, amphoteric dispersants, nonionic dispersants, and polymeric dispersants. Dispersants with an HLB value of 12 or more are preferable, and those with an HLB value of 14 or more are more preferable. The HLB value can be calculated by the following formula: Griffin method: HLB value = [(molecular weight of hydrophilic portion) ÷ (total molecular weight)] × 20
[0080] Examples of cationic dispersants include alkylamine salts having an alkyl group having 8 to 22 carbon atoms, such as stearylamine acetate, and quaternary ammonium salts, such as lauryltrimethylammonium chloride and hexadecyltrimethylammonium bromide.
[0081] Examples of the anionic dispersant include sodium alkyl sulfates having 8 to 18 carbon atoms, such as sodium lauryl sulfate; polyoxyethylene alkyl ether sulfate salts having an alkyl group having 8 to 18 carbon atoms, such as sodium polyoxyethylene lauryl ether sulfate; alkylbenzene sulfonates having an alkyl group having 8 to 18 carbon atoms, such as sodium deoxycholate and sodium dodecylbenzene sulfonate; fatty acid salts; and naphthalenesulfonic acid formalin condensates, such as the sodium salt of β-naphthalenesulfonic acid formalin condensate.
[0082] Examples of amphoteric dispersants include alkyl betaines having an alkyl group with 8 to 22 carbon atoms, and alkyl amine oxides having an alkyl group with 8 to 18 carbon atoms.
[0083] Examples of nonionic dispersants include polyoxyethylene alkyl ethers having an alkyl group with 1 to 20 carbon atoms, block copolymers composed of ethylene oxide and propylene oxide, alkylphenol polyethylene glycol ethers having an alkyl group with 1 to 20 carbon atoms, polycarboxylate ethers having an alkylene group with 2 to 4 carbon atoms, and other polyoxyalkylene derivatives; and sorbitan fatty acid esters such as sorbitan tristearate.
[0084] Examples of polymeric dispersants include cellulose derivatives such as polyvinylpyrrolidone, polyvinyl alcohol, polyvinyl butyral, hydroxycellulose, hydroxyalkylcellulose having an alkyl group having 1 to 8 carbon atoms, carboxymethylcellulose, and carboxypropylcellulose, starch, gelatin, acrylic copolymers, polycarboxylic acids or derivatives thereof, and polystyrene sulfonic acid or salts thereof.
[0085] The content of the dispersant is preferably 0.1 to 55% by weight, more preferably 1 to 30% by weight, based on the solid content of the conductive composition. Within this range, the coating properties on the substrate, the dispersion stability of the blended components, and the film strength of the conductive coating film are excellent.
[0086] <Leveling agent> Adding a leveling agent to the conductive composition improves the affinity of the conductive composition to the substrate and can suppress the occurrence of repelling and unevenness when forming a conductive coating film. Examples of the leveling agent include silicone-based leveling agents, fluorine-based leveling agents, polyether-based leveling agents, polyester-based leveling agents, and acrylic-based leveling agents.
[0087] Examples of silicone-based leveling agents include polysiloxanes; reactive polysiloxanes having reactive groups such as amino groups, epoxy groups, hydroxyl groups, and carboxyl groups introduced therein; and non-reactive polysiloxanes having non-reactive groups such as alkyl groups, ester groups, aralkyl groups, phenyl groups, and polyether groups introduced therein.
[0088] Examples of fluorine-based leveling agents include perfluoropolyether-modified polydimethylsiloxane, perfluoropolyester-modified polydimethylsiloxane, perfluorobutanesulfonic acid, fluorine-containing, hydrophilic, and lipophilic group-containing oligomers, perfluoroalkyl group-containing carboxylates, and perfluoroalkyl group- and phosphate group-containing phosphate esters.
[0089] Examples of polyether-based leveling agents include cellulose ether; pullulan; polyethylene glycol; silicone-modified polyethers such as polyether-modified polydimethylsiloxane, polyether-modified siloxane, polyetherester-modified hydroxyl group-containing polydimethylsiloxane, and polyether-modified acrylic group-containing polydimethylsiloxane; polyglycerin; polyether polyol, polyoxyethylene-polyoxypropylene condensates, polyoxyethylene alkylphenyl ethers, alkyl ether derivatives such as lauryl alcohol alkoxylate, and alkyl ether sulfates.
[0090] Examples of polyester-based leveling agents include polyester-modified acrylic group-containing polydimethylsiloxane, polyester-modified polydimethylsiloxane, and polyester polyol.
[0091] Examples of the acrylic leveling agent include acrylic copolymers made of silicone and acrylic.
[0092] The content of the leveling agent is preferably 0.1 to 20% by weight, more preferably 1 to 10% by weight, based on the solid content of the conductive composition. Within this range, the coating property on the substrate, the dispersion stability of the blended components, and the film strength of the conductive coating film are excellent.
[0093] <Crosslinking agent> Examples of the crosslinking agent include melamine-based, carbodiimide-based, oxazoline-based, epoxy-based, isocyanate-based, acrylate-based, etc. When the conductive composition contains a crosslinking agent, the content is not particularly limited, but is preferably 20% by weight or less of the solid content of the conductive composition.
[0094] <Catalyst> When the conductive composition contains a thermosetting binder or a crosslinking agent, a catalyst may be added. The catalyst is not particularly limited, and examples thereof include a photopolymerization initiator, a thermal polymerization initiator, and an acid catalyst. These may be used alone or in combination of two or more kinds.
[0095] <<Conductive coating film>> The conductive coating film of the present invention is made of the conductive composition. The method for producing the conductive coating film is not particularly limited, but the conductive coating film can be produced, for example, by a method including a step of forming a coating film of the conductive composition on a substrate and a step of drying the coating film.
[0096] The coating film is formed by applying the conductive composition onto the substrate. Examples of the coating method include blade coating, bar coating, gravure coating, roll coating, bar coating, dip coating, spin coating, casting, die coating, curtain coating, spray coating, doctor coating, slit coating, letterpress printing, screen printing, offset printing, gravure printing, spray printing, inkjet printing, and pad printing.
[0097] Before forming a coating film of the conductive composition on the substrate, the surface of the substrate may be subjected to a surface treatment in advance. Examples of the surface treatment include corona treatment, plasma treatment, itro treatment, and flame treatment. The conductive composition may be applied directly to the substrate surface, or may be applied on a separate layer such as a primer layer that is provided on the substrate in advance.
[0098] By drying the coating film formed on the substrate, the volatile components contained in the coating film are removed, and a conductive coating film is obtained. Heat drying is preferred as the drying method, and examples thereof include methods using a blast oven, an infrared oven, a vacuum oven, etc. The temperature condition during heat drying is preferably 60 to 230°C, more preferably 80 to 200°C. The treatment time of the heat treatment is not particularly limited, but is preferably 0.1 to 60 minutes, more preferably 1 to 20 minutes.
[0099] Examples of the material of the substrate include alloys such as titanium alloy, stainless steel, brass, and duralumin, pure metals such as titanium, copper, aluminum, chromium, nickel, zirconium, niobium, molybdenum, tantalum, tungsten, gold, silver, platinum, palladium, rhodium, iridium, and ruthenium, glass, polyester resins such as polyethylene terephthalate (PET), polyethylene naphthalate, and modified polyester, polyolefin resins such as polyethylene (PE) resin, polypropylene (PP) resin, polystyrene resin, and cyclic olefin resin, vinyl resins such as polyvinyl chloride and polyvinylidene chloride, polyether ether ketone (PEEK) resin, polysulfone (PSF) resin, polyether sulfone (PES) resin, polycarbonate (PC) resin, polyamide resin, polyimide resin, acrylic resin, and triacetyl cellulose (TAC) resin. The substrate may be a composite of two or more of these materials. Among these, stainless steel and titanium are preferable because they are relatively inexpensive and easy to obtain and have excellent corrosion resistance.
[0100] The thickness of the conductive coating film is preferably 100 nm to 500 μm, more preferably 100 nm to 250 μm, and further preferably 100 nm to 20 μm. The thickness of the conductive coating film can be measured using a scanning electron microscope image or a film thickness meter, and can also be calculated based on the solid content of the conductive composition used to form the conductive layer and the amount of coating on the substrate.
[0101] The conductive coating film of the present invention is physically and electrochemically stable, and therefore when used as an electrode, electrolysis can be performed at a constant current even if a high voltage is applied. The stability of the conductive coating film can be evaluated by a constant current electrolysis test. In the constant current electrolysis test, the potential is stable when the set current is low, but when the set current is increased, the coating film deteriorates and peels off, causing the potential to exceed 5 V vs. Ag / AgCl. When a 3.3 μm-thick conductive coating film of the present invention formed on a substrate was used as a test electrode and a constant current electrolysis test was performed for 90 minutes in a 0.1 M sodium sulfate aqueous solution, the electrolysis current of 11 mA / cm was obtained. 2 It is preferable that the potential is 5 V vs. Ag / AgCl or less even at the constant current of 12 mA / cm. 2 More preferably, 13 mA / cm or more 2 More preferably, 14 mA / cm 2 The upper limit of the constant current is not particularly limited, but is generally 500 mA / cm 2 The time for the constant current electrolysis test is more preferably 120 minutes, and even more preferably 150 minutes. In the constant current electrolysis test, for example, VM2 manufactured by EC Frontier can be used as the electrolysis cell. It is preferable to use a titanium substrate for the test electrode. A platinum wire can be used as the counter electrode. The electrode area of the test electrode consisting of the substrate and the conductive coating film formed on the substrate is 1 cm2. 2 It is preferable to set the above.
[0102] The conductive coating film of the present invention is physically and electrochemically stable, and therefore has a small background current when used as an electrode. The background current was measured, for example, using an electrolytic cell (EC Frontier, VM2) with a platinum wire as the counter electrode, an Ag / AgCl electrode as the reference electrode, a substrate, and a test electrode (electrode area: 1 cm) consisting of a conductive coating film formed on the substrate. 2The background current can be evaluated by performing cyclic voltammetry (CV) measurements in a 0.1M sodium sulfate aqueous solution using a 0.1M NaCl solution. The measurement potential is -1.5V to +1.5V (vs. Ag / AgCl), the scan rate is 100mV / sec, and the number of cycles is 3. The average background current measured is 1μA / cm 2 Preferably less than 0.5 μA / cm 2 More preferably, it is less than 0.25 μA / cm 2 It is even more preferable that it is less than 1000 .mu.m.
[0103] The surface resistivity of the conductive coating is 1×10 -2 ~1×10 6 Ω / □ is preferable, and 1×10 -2 ~1×10 5 Ω / □ is more preferable, and 1×10 -2 ~1×10 4 It is more preferably Ω / □.
[0104] Laminates consisting of conductive coatings and substrates have a wide potential window and suppressed background current, making them ideal for use as electrodes for highly sensitive sensors and electrodes for electrolysis in the decomposition, removal, and recycling of persistent substances. EXAMPLES
[0105] The present invention will be described below with reference to examples, but the present invention is not limited to the following examples. In the following, "parts" and "%" mean "parts by weight" and "% by weight", respectively, unless otherwise specified.
[0106] (1) Materials used (1-1) Conductive diamond particles Boron-doped diamond dispersion 1 (prepared in Example 2) Boron-doped diamond dispersion 2 (prepared in Example 3) Boron-doped diamond dispersion 3 (prepared in Example 4)
[0107] (1-2) Conductive assistant Carbon nanotube dispersion 1 (prepared in Example 5) Carbon nanotube dispersion 2 (prepared in Example 6) Graphite (powdered graphite powder manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) Conductive polymer 1 PEDOT / PSS (Heraeus, Clevios PH1000, solid content 1.1%) Conductive polymer 2 PEDOT analogue (self-doped solvent-soluble PEDOT, Tosoh Corporation, SELFTRON DN-500, solid content 1.0% (solvent PGME)) Silver nanoparticles (Mitsubishi Paper Mills, NBSIJ-MU01)
[0108] (1-3) Binder Tetraethoxysilane (Tokyo Chemical Industry Co., Ltd.) Methyl silicate oligomer (SiO2 content 52%) (Mitsubishi Chemical Corporation, MS-51) ·Silicate oligomer (KER-400, manufactured by Shin-Etsu Chemical Co., Ltd.) Acrylic resin (Nikasol RX-66E, manufactured by Nippon Carbide Industries Co., Ltd.) Polyester resin (Aronmelt PES-2405A30, manufactured by Toa Gosei Co., Ltd.) Polyurethane resin (Superflex 130, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.)
[0109] (1-4) Solvent Ethanol (Tokyo Chemical Industry Co., Ltd.) Methyl ethyl ketone (FUJIFILM Wako Pure Chemical Industries, Ltd.) Propylene glycol monomethyl ether (PGME, manufactured by Showa Denko K.K.)
[0110] (1-5) Base material Titanium base material
[0111] (2) Manufacturing of conductive diamond particles (2-1) Production Example 1 (Boron-doped Diamond 1) Using diamond powder (manufactured by Element Six, Micron+MDA0-0.5, average particle size: approximately 300 nm) as a substrate, a BDD layer was grown on the substrate surface by the microwave plasma CVD method to fabricate as-grown BDDP. An acetone-methanol mixed solution (9:1, v / v) was used as the carbon source, and trimethoxyborane was used as the boron source, and the ratio of the number of boron atoms to the number of carbon atoms (boron / carbon) was set to 20,000 ppm. The CVD conditions are shown below. The as-grown BDDP was subjected to heat oxidation treatment (oxygen termination treatment) at 425 °C for 5 hours in air using a muffle furnace to obtain BDDP. <CVD Conditions> Microwave output: 1300 W Pressure: 50 Torr Hydrogen gas flow rate: 400 sccm Boron / carbon ratio: 20,000 ppm Growth time: 8 h The average particle size of the obtained BDDP was 350 nm, and the oxygen atom concentration on the BDDP surface was 7.6%.
[0112] (2-2) Production Examples 2 to 6 (Production of Boron-Doped Diamond Dispersion and Carbon Nanotube Dispersion) Each component was mixed at the weight ratio shown in Table 1, and pre-dispersion and main dispersion were performed. The particle size and dispersibility of the particles contained in the obtained dispersion are shown in Table 1. The dispersibility was evaluated as good when no sediment was visually confirmed immediately after dispersion.
[0113]
Table 1
[0114] (3) Production of Conductive Composition and Conductive Laminate (Examples 1 to 15, Comparative Examples 1 to 4) Each component described in Table 2 was mixed to prepare a conductive composition. In Table 2, the amounts of the conductive diamond particles, conductive auxiliary agent, and binder indicate the weight ratio of the solid content. The conductive composition was adjusted to the solid content ratio described in Table 2 using a solvent.
[0115] The conductive composition was applied to one side of a titanium substrate by drop casting and dried at 200°C for 20 minutes using a blower dryer to form a conductive coating film on the substrate. The thickness of the conductive layer was adjusted to the film thickness shown in Table 2 by appropriately adjusting the amount of the drop. The conductive coating film was evaluated by the following method. The results are shown in Table 2.
[0116] (4) Evaluation method for conductive coating film (4-1) Current density An electrolytic cell (EC Frontier, VM2) was used, and the test electrodes (electrode area: 1 cm ) obtained in Examples 1 to 15 and Comparative Examples 1 to 4 were electrochemically measured using a platinum wire as the counter electrode. 2 ) was subjected to constant current electrolysis in a 0.1M sodium sulfate aqueous solution. In the constant current electrolysis test, when the set current was low, the potential did not rise and was stable, but when the set current was increased, the coating film deteriorated and peeled off, and the potential exceeded 5V vs. Ag / AgCl over time. Table 2 shows the maximum current density at which the potential did not exceed 5V vs. Ag / AgCl even after 90 minutes of electrolysis.
[0117] (4-2) Background current An electrolytic cell (EC Frontier, VM2) was used, with a platinum wire as the counter electrode and an Ag / AgCl electrode as the reference electrode, and the test electrodes (electrode area: 1 cm ) obtained in Examples 1 to 15 and Comparative Examples 1 to 4 were 2 ) was used to perform CV (cyclic voltammetry) measurements in a 0.1M sodium sulfate aqueous solution. The measurement potential was -1.5V to +1.5V (vs. Ag / AgCl), and the scan rate was 100mV / sec. The number of cycles was set to 3, and the average value of the measured background current was calculated and evaluated according to the following criteria. Background current is 1μA / cm 2 Less than: 〇 Background current is 1μA / cm 2 More than: ×
[0118] (4-3) Reproducibility of background current The background current measurement described in (4-2) above was performed using multiple electrode samples (n=5) prepared under the same conditions, and the coefficient of variation (A(%)) of the background current was calculated. In addition, the background current was measured repeatedly (n=3) using the same electrode sample, and the coefficient of variation (B(%)) of the background current was calculated. The reproducibility was evaluated according to the following criteria based on the values of A and B. Both A and B are within 5%: Yes Either A or B exceeds 5%: ×
[0119] [Table 2]
[0120] In Comparative Example 1, which did not contain a conductive assistant, and Comparative Example 2, which used silver nanoparticles as a conductive assistant, the current density was low and the reproducibility of the background current was low. In Comparative Examples 3 and 4, which did not contain boron-doped diamond, a large background current was observed. In Examples 1 to 15, the current density was high, the background current was small, and the reproducibility was high.
[0121] The invention according to the present disclosure may include, for example, the following aspects. <1> A conductive composition comprising conductive diamond particles, a conductive assistant comprising a non-particulate conductive component, and a binder.
[0122] <2> When a 3.3 μm-thick conductive coating film made of the conductive composition formed on a substrate was used as a test electrode and a constant current electrolysis test was carried out for 90 minutes in a 0.1 M sodium sulfate aqueous solution, a constant current of 11 mA / cm was obtained. 2 Item 2. The conductive composition according to item 1, wherein the potential is 5 V vs. Ag / AgCl or less even at a constant current of 10 V or less.
[0123] <3> Item 3. The conductive composition according to item 1 or 2, wherein the conductive diamond particles are boron-doped diamond.
[0124] <4> 4. The conductive composition according to any one of items 1 to 3, comprising 0.01 to 800 parts by weight of a conductive assistant relative to 100 parts by weight of conductive diamond particles.
[0125] <5> 5. The conductive composition according to any one of items 1 to 4, wherein the conductive assistant comprises at least one selected from the group consisting of a conductive polymer, a carbon material, and a metal nanowire.
[0126] <6> Item 6. The conductive composition according to item 5, wherein the conductive polymer is one or more selected from the group consisting of polythiophene, polypyrrole, and polyaniline.
[0127] <7> Item 6. The conductive composition according to item 5, wherein the carbon material is one or more selected from the group consisting of carbon nanotubes, graphene, and graphite.
[0128] <8> Item 6. The conductive composition according to item 5, wherein the metal material is one or more selected from the group consisting of silver nanowires, copper nanowires, and gold nanowires.
[0129] <9> Item 9. A conductive coating film comprising the conductive composition according to any one of items 1 to 8.
Claims
1. A conductive composition comprising conductive diamond particles, a conductive assistant comprising a non-particulate conductive component, and a binder.
2. When a 3.3 μm-thick conductive coating film made of the conductive composition formed on a substrate was used as a test electrode and a constant current electrolysis test was carried out for 90 minutes in a 0.1 M sodium sulfate aqueous solution, the current density was 11 mA / cm 2 The conductive composition according to claim 1, wherein the potential is 5 V vs. Ag / AgCl or less even at a constant current of 10 V or more.
3. 3. The conductive composition of claim 1 or 2, wherein the conductive diamond particles are boron doped diamond.
4. 3. The conductive composition according to claim 1, further comprising 0.01 to 800 parts by weight of a conductive assistant per 100 parts by weight of conductive diamond particles.
5. 3. The conductive composition according to claim 1, wherein the conductive assistant comprises at least one selected from the group consisting of a conductive polymer, a carbon material, and a metal material.
6. 6. The conductive composition according to claim 5, wherein the conductive polymer is at least one selected from the group consisting of polythiophene, polypyrrole, and polyaniline.
7. The conductive composition according to claim 5 , wherein the carbon material is at least one selected from the group consisting of carbon nanotubes, graphene, and graphite.
8. The conductive composition according to claim 5 , wherein the metal material is at least one selected from the group consisting of silver nanowires, copper nanowires, and gold nanowires.
9. A conductive coating film comprising the conductive composition according to claim 1 or 2.
Citation Information
Patent Citations
Method for manufacturing diamond electrode
JP2007238989A
Conductive diamond particle, conductive diamond electrode, and inspection device
JP2018076216A
Diamond electrode, manufacturing method of diamond electrode, and coating method of conductive diamond
JP2020199478A
Electrically conductive diamond electrode, production method thereof and electrolysis unit
JP2022089096A